2001
DOI: 10.1016/s0928-8244(01)00259-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of intranasally inoculated Lactobacillus fermentum against Streptococcus pneumoniae challenge on the mouse respiratory tract

Abstract: Lactic acid bacteria are increasingly used to restore the ecological equilibrium of different mucosal areas in humans and/or animals. Likewise, they can be used to potentially protect against pathogenic microorganisms. In the present paper, the preventive effect of intranasally inoculated Lactobacillus fermentum against challenge with Streptococcus pneumoniae was studied, using a mouse experimental model. L. fermentum inoculated four times at a dose of 10(7) colony forming units per mouse was able to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…44 Hussell and Humphreys 45 suggested that NALT could fulfill an important role by reducing the pathogen burden to a level that would induce only minimal inflammation in the lower lung. Using an experimental model of S. pneumoniae infection, Cangemi de Gutierrez et al 46 showed that the preventive intranasal inoculation of Lactobacillus fermentum caused a decrease in the number of pathogens throughout the respiratory tract together with an increase both in the number of activated macrophages in lung and in the lymphocyte population in the tracheal lamina propria. On the other hand, recombinant L. lactis NZ 9000 has been proven to elicit an immune response after inoculation by different mucosal routes.…”
Section: Lactococcus Lactis Nasally Administered As An Adjuvant and Dmentioning
confidence: 99%
“…44 Hussell and Humphreys 45 suggested that NALT could fulfill an important role by reducing the pathogen burden to a level that would induce only minimal inflammation in the lower lung. Using an experimental model of S. pneumoniae infection, Cangemi de Gutierrez et al 46 showed that the preventive intranasal inoculation of Lactobacillus fermentum caused a decrease in the number of pathogens throughout the respiratory tract together with an increase both in the number of activated macrophages in lung and in the lymphocyte population in the tracheal lamina propria. On the other hand, recombinant L. lactis NZ 9000 has been proven to elicit an immune response after inoculation by different mucosal routes.…”
Section: Lactococcus Lactis Nasally Administered As An Adjuvant and Dmentioning
confidence: 99%
“…However, experimental studies on animal models support the hypothesis for a potentially beneficial effect of probiotics on human RTIs. This could be mediated by the stimulation of cellular and humoral immunological functions [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This concept implies that oral immune stimulation can induce immunity in distal intestinal mucosal sites. For instance, the consumption offermented milk has been related to a reduced incidence of nasal pathogens (24)(25)(26). The majority of research concerning probiotic-mediated enhanced immune protection has focused on the gastrointestinal tract, and few studies have been conducted to consider the possibility that probiotics might stimulate the common mucosal immune system sufficiently to provide increased protection to other mucosal sites as well (27).…”
mentioning
confidence: 99%